Evaluasi Usability pada SIMPEL SMAN 12 Semarang dengan Metode Usability Testing - Wahyuningtyas Hesti; Iwan Setiawan Wibisono (Universitas Ngudi Waluyo, 2022)
Abstrct — The Learning Management System (SIMPel) of SMAN 12 Semarang is a system that provides features that are used to facilitate online learning. The online learning system in a school plays a significant role because it can improve the learning process. This study aims to measure the usability of SIMPel SMAN 12 Semarang. There are four aspects of usability used in this study: effectiveness, efficiency, learnability, and satisfaction, which are then used as aspects of assessment. This research was conducted to determine the usability of the system for users by analyzing the problems faced by users when using the system. A total of 13 research respondents consisting of 3 administrative staff respondents, five teacher respondents, and five student respondents, were selected to perform usability testing on the system. From the results of the system evaluation conducted with administrative staff and teacher respondents, it was found that the effectiveness aspect reached 97.5%, the efficiency aspect was 95.5%, the learnability aspect was 94%, and the satisfaction aspect got 88%. Meanwhile, the results of tests carried out on the system with alumni respondents showed that the effectiveness aspect reached 100%. The ef_ciency aspect was 100%, the learnability aspect was 93.6%, and the satisfaction aspect was 88.8%. From these results, it can be concluded that SIMPel SMAN 12 Semarang is a very feasible system to use, and the system can be used according to user needs. The results of interviews with respondents resulted in recommendations that could then be used to improve the system. Keywords: Evaluation, The Learning Management System, Usability, Usability Testing